perbandingan kurikulum merdeka dan kurikulum 2013 terhadap peningkatan kreativitas peserta didik di SMPN 21 Mataram - Saputri, Tri; Rispawati; Basariah; Mustari, Mohammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the comparison between the Merdeka Curriculum and the 2013 Curriculum on enhancing students' creativity. The research employed a quantitative approach with an ex-post facto design. The sample consisted of two classes selected through purposive sampling technique, namely class VIII A with 25 students and class IX A with 27 students. The research instrument was a validated and reliable creativity enhancement questionnaire. Data were analyzed through prerequisite tests (Kolmogorov-Smirnov normality test and homogeneity significance test), followed by hypothesis testing using One-Way ANOVA. The analysis results showed a significance value of 0.017 < 0.05, with a mean score of students' creativity enhancement of 44.120. These findings indicate that there is a significant difference between the Merdeka Curriculum and the 2013 Curriculum in terms of enhancing students' creativity.